Sudden hearing loss following acute carbon monoxide poisoning: A case report and literature review. Issue 1 (February 2023) - Li, Chiao-Zhu; Li, Chiao-Ching; Lin, Meng-Chi; Tseng, Wei-Shih
Introduction: Acute carbon monoxide (CO) poisoning could lead to headache, dizziness, myocardial injury, neurological sequela, and death. Sudden hearing loss is a rare symptom of acute CO poisoning. Case Presentation: Here, we report a case of a 42-year-old woman who suffered from acute hearing loss after exposure to a suicidal environment of high concentration of CO. Partial recovery of hearing was demonstrated after a combination of corticosteroid and hyperbaric oxygen therapy was given. Discussion: The mechanism of sudden hearing loss caused by acute CO poisoning is not well-established. It is believed to be related with the hypoxic damage to the cochlea. The characteristic of sudden hearing loss caused by acute CO poisoning is that it often affects in high frequency bilaterally. Conclusion: This report would prompt the clinician in early recognition of this sudden hearing loss of uncommon etiology.